Encountering Ageing Women: Ambiguous Representations of the Elderly in Early Modern Literary Fairy Tales - Ardeni, Viola (Quaderni d'Italianistica)

(untitled) (Iter Press, 2021)
This essay offers a comparative analysis of two early modern literary representations of the encounters between a pair of ageing sisters and a king, a barber, and a group of fairies. The representations occur in the literary fairy tale “La vecchia scortecata” (“The Old Woman Who Was Skinned”), which appears in the Neapolitan text by Giambattista Basile, Lo cunto de li cunti (The Tale of Tales, 1634–36), and in “La Fola dla Vecchia Scurtgà” (“The Tale of the Old Skinned Woman”), featured in Lo cunto de li cunti’s translation in Bolognese, La chiaqlira dla banzola (The Chatterer on the Bench, 1742) by Maddalena and Teresa Manfredi and Angela and Teresa Zanotti. The multilingual literary encounters not only bring forth anxieties related to decay and the ageing of things contemporaneous to the writing of both works but they also display how ageing women have been conceived as an ambiguous aberration—an abject, in Julia Kristeva’s conceptualization—within the fictional universe of seventeenth- and eighteenth-century literary fairy tales. It is thus postulated that ageing in women is an intolerable characterization within the fairy-tale ecosystem while an unavoidable one. The essay finally shows how the two women’s co-existence is destabilizing in nature and problematizes heteronormative conventions regarding the institution of family and reproductive norms.